Baseline concussion assessment performance of community-based senior rugby players: a cross-sectional study. (19th September 2021) - Salmon, Danielle M.; Chua, Jason; Sullivan, S. John; Whatman, Chris; Brown, James; Register-Mihalik, Johna; Murphy, Ian; Walters, Simon; Clacy, Amanda; Sole, Gisela; Kerr, Zachary Y.; Rasmussen, Karen; et al.
ABSTRACT: Objective: To report pre-season baseline concussion assessment performance among senior rugby players and explore associations between assessment performance and player demographics. Design: A cross-sectional study using the New Zealand Rugby Concussion Assessments (NZRCA), comprising symptom, cognitive and dynamic coordination assessments was conducted in the 2018–2019 season. Methods: Players' baseline assessments were characterised using descriptive statistics; effect sizes (ES) and t-tests were used to explore associations between player demographic characteristics and NZRCA performance. Results: A total of 733 players (11.4% female) aged between 16 and 52 years completed the NZRCA. The median (range) value for symptom severity, endorsed symptoms and "percentage normal" was respectively, 5 (0–40), 5 (0–21) and 90% (30–100%). A perfect standardised assessment of concussion score was achieved by one participant; seven achieved ≥27/30 for immediate recall, and 22 achieved a perfect delayed recall score. Most participants (n = 674, 92%) passed the tandem gait test. Associations between NZRCA performance and gender, concussion history, and Pasifika ethnicity were observed with effect sizes ranging from small (0.18) to large (0.70). Six hundred and twenty-three (85%) participants reported at least one symptom. Conclusions: The results from this study could help support decision-making by clinicians, improving the management of concussions in the community setting.